Fragile X-Associated Disorders in Serbia: Baseline Quantitative and Qualitative Survey of Knowledge, Attitudes and Practices Among Medical Professionals - Budimirovic, Dejan B.; Cvjetkovic, Smiljana; Bukumiric, Zoran; Duy, Phan Q.; Protic, Dragana (Frontiers in Neuroscience, 2018)
We conducted a knowledge, attitude, and practice (KAP) survey of fragile X-associated disorders (FXD) in Serbia in order to obtain baseline quantitative and qualitative KAP data on fragile X mental retardation 1 gene (FMR1) pre- and full mutations (PM, FM). The survey’s 16-item questionnaire included a knowledge component (12/16), such as self-assessment knowledge (SAK) and factual knowledge (FK, 2/5 questions for PM, FXTAS and FXPOI). Education-directed attitudes in the FXD field and FMR1 DNA testing practices had 4/16 items, including brief case vignettes of FXTAS and FXPOI, respectively. The study’s cohort consisted of primary care physicians (referred to as “physicians” in the rest of the text) throughout Serbia (n=284, aged 26-64 years, 176/284, 62.2% in Belgrade, Serbia) and senior medical students (n=245, aged 23-30 years; 33.5% males) at the Belgrade School of Medicine. Strikingly, half of the survey respondents indicated “not having any” knowledge for the fragile X gene premutation and FXD. Physicians were more likely to indicate “not having any” knowledge than students (41.2% of physicians vs. 13.1% of students, P<0.05). Roughly half of the students had “minimal knowledge” (53.5% vs. 30.5% of physicians, P<0.05). Low FK was common in the cohort, as few physicians had “all correct answers” (7.5% vs. 3.7% of students, P<0.05; 16.5% vs. 9.5% of students for the 2/5 premutation-related questions). Statistical analyses identified physicians’ practice setting and length of clinical experience as predictors of the lack of FK on questions related to FXD. Physicians were more likely than students to indicate “strongly agreed” to expand their knowledge of the gene premutation and FXD (90.9% vs. 66.7% of students, P<0.01). However, students more frequently indicated that they are willing to recommend DNA testing in their future practices than physicians (93.5% vs 64.8% of physicians, P<0.001). In conclusion, there is a major gap in knowledge regarding fragile X gene PM and FXD among the study's participants in Serbia. The study’s informative-educational survey serves as an initial step in the process of enhancing the KAP of medical professionals with regards to the fragile X gene premutation and FXD.